2010
DOI: 10.1002/pds.1912
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiological research using French reimbursement databases: yes we can!

Abstract: The French reimbursement databases were greatly used over the last 20 years. They can provide data on exposure to drugs and can be used to study patterns of drug utilization although their limitations must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 82 publications
0
93
0
1
Order By: Relevance
“…Moreover, the analysis of the reimbursement database showed that Skenan was the first prescribed morphine sulfate in France during the period 2002–2007 [23]. This database includes dispensing of reimbursed drugs to all subjects enrolled in the general health insurance scheme, which covers approximately 74% of the French general population [24]. These data are not sufficient to explain why Skenan is the most abused morphine sulfate in France since morphine sulfate is widely prescribed for pain related to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of the reimbursement database showed that Skenan was the first prescribed morphine sulfate in France during the period 2002–2007 [23]. This database includes dispensing of reimbursed drugs to all subjects enrolled in the general health insurance scheme, which covers approximately 74% of the French general population [24]. These data are not sufficient to explain why Skenan is the most abused morphine sulfate in France since morphine sulfate is widely prescribed for pain related to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Erasme includes a large population and most of the drugs marketed in France. Thus, this database has been extensively used for 20 years for epidemiologic and pharmacoepidemiologic research [24]. It is crucial to know the structure of a database, especially if it was not originally developed for pharmacoepidemiological research.…”
Section: Discussionmentioning
confidence: 99%
“…Second, patients included in the study were a representative sample of the local population, as consecutive patients over a 7-month period within a given geographic area were included. Finally, the treatments studied here have a low or null proportion of over the counter, thereby implying a high degree of capture in the French national health insurance system database [18]. …”
Section: Discussionmentioning
confidence: 99%
“…It covers all the reimbursement data for all patients, including drugs and tests ordered by physicians and presented for reimbursement [16]. Organization of data collection and database has been described in detail previously [17, 18]. This database provides information on drug characteristics, number of purchases and dosage for each purchase.…”
Section: Methodsmentioning
confidence: 99%